mTOR Signaling in the Regulation of CD4+ T Cell Subsets in Periodontal Diseases - Jiang, Qian; Huang, Xiaobin; Yu, Wenjing; Huang, Ranran; Zhao, Xuefeng; Chen, Chider (Frontiers in Immunology, 2022)
Periodontal disease results from the inflammatory infiltration by the microbial community which is marked through tooth mobility and alveolar bone resorption. The inflammation in periodontal disease is mediated by CD4+ T cells through cytokine secretion and osteoclastogenetic activity. The inflammatory model in periodontal disease is described through disruption of the balance between two subsets of T helper cells which are T-helper type 1 (Th1) and T-helper type 2 (Th2). In recent studies, apart from subsets of helper T cells, regulatory T-cells and Th17 have been proposed to induce the pathogenesis of periodontal diseases. Growing evidence proves that helper T cells differentiation, activation, and subset determination are under the strong impact of mTOR signaling. This review aims to integrate the topical researches about the role of different types of Th cells in the pathogenesis of periodontal diseases, as well as the regulation of mTOR signaling in the specification and selection of Th cell commitment.